THE ENGLISH UTILITARISM DOCTRINE IN THE COLOMBIAN UNIVERSITY OF THE XIX CENTURY (2011)
In the new Grenada, today Republic of Colombia, for the first time, English author Jeremy Bentham was mentioned, when in the newspaper “La Bagatela”, Antonio Nariño published an article highlighting his work in 1811. Many people such as Antonio Nariño, Simón Bolívar and Francisco de Paula Santander, using their correspondence system, comments about other authors and Jeremy Bentham’s text analysis, knew the utilitarian doctrine approach. They deemed it interesting and useful and applicable to that time projects. This is why they decided to include it in the Civil and Penal Law taught in the universities and high-schools. Thus, Bentham helped Santander’s educational project carried out a great deal as well as those of the radical Colombian governments in the second half of the nineteenth century, especially regarding the establishment of the secular school.